George Frederic Matthew's Contribution to Precambrian Paleobiology - Miller, Randall (Geoscience Canada, 2003)
Summary George Frederic Matthews description of the Precambrian stromatolite Archaeozoon acadiense, one of the first authentic, documented Precambrian fossils, is perhaps the most overlooked of his many accomplishments. It was the first Precambrian stromatolite to receivea Linnéan name and may have been the first photographed for a scientific publication. Matthew's contribution is recognized by experts in the field and inspecialized literature about stromatolites.However, it is rarely mentioned in the popular history of the search for Precambrian life which generally includes stories of Dawson's Eozooncanadense, and Walcott's Cryptozoon andChuaria. Although the American geologist Charles Doolittle Walcott is viewed as the founder of Precambrian paleobiology, Matthew deservesacknowledgment for his early recognition of Precambrian life. A well-known figure among specialists, Matthew never attained the status ofsome of his peers and is generally not known as an important Canadian geoscientist. Employed as a customs agent and not as a paleontologist, he was never able to pursue any single field of paleontology with the resources available to his colleagues. Matthew described Archaeozoon acadiense in the Bulletin of the Natural History Society of New Brunswick. While the Bulletin had reasonable circulation among geoscientists in Matthew's day, it ceased publication in1917 and is rarely seen. Perhaps his choice of a journal to report the stromatolite contributed to his work not being widely acknowledged.